Diagnosis and Epidemiology of Helicobacter pylori Infection. (9th September 2013) - Calvet, Xavier; Ramírez Lázaro, María‐José; Lehours, Philippe; Mégraud, Francis
Abstract: A limited amount of new information was published in the field of diagnosis and epidemiology of Helicobacter pylori this last year. Besides some improvement in current tests, it is interesting to note the attempts to identify severe disease, for example gastric cancer, by breath analysis using nanomaterial‐based sensors. In contrast, the predictive value for gastric cancer and atrophy of pepsinogen determinations was found inadequate. Prevalence studies of H. pylori infection have been carried out in adults and children around the world in the general population but also in specific communities. The usual risk factors were found. In addition, a Japanese study highlighted the role of grandmothers in the familial transmission of H. pylori . A study showed that the infection may not always readily establish itself in children, given the number of transient infections observed. It was also noted that after eradication, a first‐year relapse is likely to be a recurrence of the previous infection, while later on it is probably a reinfection with a new strain.